MEASUREMENT INVARIANCE ACROSS AGE GROUPS OF THE ARMENIAN INSTRUMENT OF CULTURAL LOGICS OF HONOR, DIGNITY AND FACE - Grigoryan, Ani (Modern Psychology, 2023)
This article is part of ongoing studies aimed at validating the measurement model of honor, face, and dignity in the Armenian language. Psychometric equivalence of cultural logics of honor, face, and dignity across age groups was assessed.In total, 382 participants aged 18 to 47 (Mage=24.03, SD=5.721, 68.5% were women) were included in the analysis. Two age groups (youngsters, aged 18 to 25, n=273 and adults, aged 26 to 47, n=109) were defined for measurement invariance analysis. Multiple group confirmatory analyses were conducted within four model parameters: configural, metric, scalar, and residual invariance. Full invariance was achieved for the cultural logic of face across two age groups. Partial residual invariance was established for the cultural logic of honor. The cultural logic of dignity was partially invariant based on metric and scalar levels.These findings provide a psychometric basis for the valid comparisons of the means of cultural logics of honor, dignity and face across age groups.  This enriches our understanding of the Armenian instrument's performance and makes it a useful tool for social-psychological studies examining the prevalence of these cultural logics and their associations with other variables such as moral values and self-construal. Further analysis can focus on exploring the peculiarities of the non-invariant items.
Keywords: Cultural logics of honor, face and dignity; validation; measurement invariance; multiple group confirmatory analysis